Perception of creaminess in foods. Issue 3 (21st February 2020) - Upadhyay, Rituja; Aktar, Tugba; Chen, Jianshe
Abstract: Food texture and mouthfeel play a crucial role in product and consumer acceptability. Creaminess, enjoyed by consumers, is a complex, multimodal sensory perception involving olfactory, gustatory and tactile cues. Oral viscosity and lubrication are the key underlying physical properties that define the mechanism of creaminess perception. Thickness, smoothness, mouth‐coating, and dairy flavor can together play roles in the sensation of creaminess. The aim of this review is to present an understanding of the term" creaminess" along with different modalities involved in its perception, and to explore the oral physiological parameters and key physical properties that may be involved in the different oral modalities. An analysis of the previously examined links between food structure and composition and oral physiological parameters is presented. The review also presents a brief summary of previous models describing contributions of taste, aroma, and textural sensations. It emphasizes on the role of oral processing in testing proposed models with experimental evidence supporting those models and the future trends to enhance creaminess. Abstract : Mechanoreceptor: a sense organ that is designed to respond to sense and detect any physical/mechanical stimulus exerted on tissue surface and are directly responsible for food texture sensation.